2016
DOI: 10.1017/s0954579416000456
|View full text |Cite
|
Sign up to set email alerts
|

Infant autonomic nervous system response and recovery: Associations with maternal risk status and infant emotion regulation

Abstract: This study examined whether risk status and cumulative risk were associated with autonomic nervous system reactivity and recovery, and emotion regulation in infants. The sample included 121 6-month-old infants. Classification of risk status was based on World Health Organization criteria (e.g., presence of maternal psychopathology, substance use, and social adversity). Heart rate, parasympathetic respiratory sinus arrhythmia, and sympathetic preejection period were examined at baseline and across the still fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 68 publications
(133 reference statements)
5
69
1
Order By: Relevance
“…(); Suurland et al. ()). The prenatal cumulative risk score ranged from 0 to 3: 59.9% had no risk factors, 21.1% had one risk factor, 14.9% had two risk factors, and 4.3% had three risk factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(); Suurland et al. ()). The prenatal cumulative risk score ranged from 0 to 3: 59.9% had no risk factors, 21.1% had one risk factor, 14.9% had two risk factors, and 4.3% had three risk factors.…”
Section: Methodsmentioning
confidence: 99%
“…Prenatal cumulative risk was computed by adding the number of risk factors present during the first data wave (Mejdoubi et al, 2011;World Health Organization, 2005) (Norbeck, Lindsey, & Carrieri, 1981, 1983, and (j) being single (see for more detailed information about the criteria: Smaling et al (2015); Suurland et al (2017)). The prenatal cumulative risk score ranged from 0 to 3: 59.9% had no risk factors, 21.1% had one risk factor, 14.9% had two risk factors, and 4.3% had three risk factors.…”
Section: Prenatal Riskmentioning
confidence: 99%
“…For the current study, data from the Mother–Infant Neurodevelopment Study in Leiden (MINDS‐Leiden, The Netherlands; Smaling et al, ; Suurland et al, ) were used. MINDS‐Leiden is a longitudinal study examining the neurobiological and neurocognitive predictors of early behavior problems.…”
Section: Methodsmentioning
confidence: 99%
“…Sympathetic activity can be measured by pre‐ejection period, which represents the time between the depolarization of the left ventricle (onset of the heartbeat) and the onset of the left ventricular ejection of blood into the aorta. Although measurement of sympathetic activity by skin conductance level is more common, pre‐ejection period is considered a more direct indicator of cardiac sympathetic activity that can reliably be used in infancy (Alkon et al, ; Cacioppo et al, ; Suurland et al, ). Increased sympathetic activity in response to emotional challenge, which is reflected by shortening of the pre‐ejection period, has been associated with fewer behavioral problems (Boyce et al, ; Stifter et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our aim was to predict empathy from emotional responses in early infancy. Although emotional responses are present from birth, they were examined at age 6 months because previous studies indicated that physiological measurements can only be considered reliable from age 6 months (Alkon et al, ; Cacioppo et al, ; Suurland et al, ). As discussed above, empathic distress (ie, personal distress and comfort seeking) is clearly present early in development, but becomes relatively less important in early childhood.…”
Section: Introductionmentioning
confidence: 99%